Secrecy - Galison, Peter; Moss, Robb (USA, 2008)
This arresting documentary explores what it means for a democratic society when its government withholds information from its citizens. Under what circumstances, if any, is such secrecy justified? How can we know what our government is not telling us? Using interviews with people from the Central Intelligence Agency, the National Security Agency, reporters, and individuals whose lives have been marked by their contact with the national security bureaucracy, the film probes secrecy's relationship to fear, executive power, and national security. Making use of art installations, original music, and animation by Harvard University's Ruth Lingford, the film gives shape and scale to secrecy's vast, invisible presence in our democracy.
Keywords: Documentary films